2022
DOI: 10.1029/2022gl099276
|View full text |Cite
|
Sign up to set email alerts
|

Ice‐Marginal Proglacial Lakes Across Greenland: Present Status and a Possible Future

Abstract: The future evolution of the Greenland Ice Sheet (GrIS) is of global concern because its meltwater runoff will contribute tens to hundreds of millimeters of sea level rise through the next century (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Numerical models of glacier evolution should become mindful of changing terminus environments. Given that we find 242 fewer marine terminating GICs in 2001 than during the LIA termination and that the number of lake-terminating GICs have increased slightly by 24 (Figure 3), we interpret that (a) many GICs that were marine-based during the LIA are now terminating on land, and (b) some GICs have developed ice-marginal lakes at their termini as those lakes have formed in the last few decades and inside LIA moraine ridges, for example, as shown across Greenland by How et al (2021), Carrivick, How, et al (2022. The influence of lake effects on glacier mass balance (e.g., Carrivick, Tweed, et al, 2020), in addition to climate forcing, could explain why the greatest changes of mass loss have occurred for lake-terminating glaciers, which is an association that we find exists to a greater or lesser extent in all Greenland regions (Figure 3).…”
Section: Mass Balancementioning
confidence: 70%
“…Numerical models of glacier evolution should become mindful of changing terminus environments. Given that we find 242 fewer marine terminating GICs in 2001 than during the LIA termination and that the number of lake-terminating GICs have increased slightly by 24 (Figure 3), we interpret that (a) many GICs that were marine-based during the LIA are now terminating on land, and (b) some GICs have developed ice-marginal lakes at their termini as those lakes have formed in the last few decades and inside LIA moraine ridges, for example, as shown across Greenland by How et al (2021), Carrivick, How, et al (2022. The influence of lake effects on glacier mass balance (e.g., Carrivick, Tweed, et al, 2020), in addition to climate forcing, could explain why the greatest changes of mass loss have occurred for lake-terminating glaciers, which is an association that we find exists to a greater or lesser extent in all Greenland regions (Figure 3).…”
Section: Mass Balancementioning
confidence: 70%
“…None of our study areas contain large land-terminating glaciers by the end of our study period and this ice volume loss method cannot be applied to tidewater glaciers, so we do not assess the relative changes of land, lake, and marine terminating glaciers. Both numerical models (e.g., Sutherland and others, 2020; Carrivick and others, 2022) and remote observations (e.g., Baurley and others, 2020; Mallalieu and others, 2021; Carrivick and others, 2022) ranging from New Zealand to Greenland have shown that ice-contact lakes may both initiate and accelerate glacier retreat. Our results are consistent with this and further emphasize that ice-contact lakes must be accounted for when forecasting future ice volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the water contact of the glacier ice and the related thermallydriven circulation of water in the proglacial water bodies, ice-marginal lakes can be important for glacier ablation and ice dynamics (Carrivick et al, 2022b(Carrivick et al, , 2022cCarrivick & Tweed, 2013;Truffer & Motyka, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of debris cover and its thickness affects ablation as empirically observed (Østrem, 1959) and described in a theoretical model of glacial melting (Evatt et al, 2015). Due to the water contact of the glacier ice and the related thermally‐driven circulation of water in the proglacial water bodies, ice‐marginal lakes can be important for glacier ablation and ice dynamics (Carrivick et al, 2022b, 2022c; Carrivick & Tweed, 2013; Truffer & Motyka, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation